ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN TRITERPENOID DARI EKSTRAK n- EKSANA DAUN KEPUH (Sterculia foetida L.) SERTA UJI AKTIVITAS ANTIRADIKAL BEBAS - I. A. R. Astiti Asih; I W. G. Gunawan; N. M. Desi Ariani (Jurnal Kimia (Journal of Chemistry), 2010)
Kepuh leaves can be used as traditional medicine to cure various diseases. Maseration of ± 1000 g drypowder of Kepuh leaves with n-hexane as the solvent resulted in 2,10 g n-hexane concentrated extract. Separation ofthis extract with column chromatography gained two yellow amorphous crystal isolates of F3.1 and F3.2 with 0,0195 gand 0,0032 g in weight, respectively.The result of phytochemical test of isolate F3.1 with Liebermann-Burchard reagent showed that the isolatepositively contained triterpenoid. Identification of isolate F3.1 with spectrophotometer UV-Vis showed one broadpeak at 265 nm. The transition occured probably was n *, that was caused by C=O chromophor. Infraredspectrum showed characteristic groups of OH at 3294,42 cm-1, aliphatic CH at 2924,09 cm-1 and 2854,65 cm-1, C=Oat 1743,65 cm-1, bending CH2 and bending CH3 at 1458,18 cm-1 and 1381,03 cm-1 and alcoholic CO at 1172,72 cm-1.Free antiradical activity test against isolate F3.1 was carried out by spectroscopy UV-Vis method. Isolate F3.1 hadcharacteristic as a free antiradical with DPPH damping percentage at the 5th minute was 85,33% and at the 60thminute was 88,52%.According to phytochemical tests and spectrophotometry analysis, isolates from kepuh leaves was expectedto contain true triterpenoid group compounds with free antiradical activity OH group, aliphatic CH, C=O andalcoholic C-O as the functional groups.